The 2007 meltdown in structured securitization : searching for lessons, not scapegoats - Caprio, Gerard 1982- (Policy research working paper, 2008)
"The intensity of recent turbulence in financial markets has surprised nearly everyone. This paper searches out the root causes of the crisis, distinguishing them from scapegoating explanations that have been used in policy circles to divert attention from the underlying breakdown of incentives. Incentive conflicts explain how securitization went wrong, why credit ratings proved so inaccurate, and why it is superficial to blame the crisis on mark-to-market accounting, an unexpected loss of liquidity, or trends in globalization and deregulation in financial markets. The analysis finds disturbing implications of the crisis for Basel II and its implementation. The paper argues that the principal source of financial instability lies in contradictory political and bureaucratic incentives that undermine the effectiveness of financial regulation and supervision in every country in the world. The paper concludes by identifying reforms that would improve incentives by increasing transparency and accountability in government and industry alike. "--World Bank web site